Six new species of Epicephala Meyrick, 1880 (Lepidoptera: Gracillariidae) associated with Phyllanthaceae plants - Zhang, Jing; Hu, Bingbing; Wang, Shuxia; Li, Houhun (Zootaxa, 2012)
Six new species of Epicephala Meyrick, 1880 are described based on the specimens collected or reared from Breynia andGlochidion plants during a biological survey: E. lanceolaria sp. nov., E. lativalvaris sp. nov., E. mirivalvata sp. nov., E.vitisidaea sp. nov., E. bipollenella sp. nov., and E. eriocarpa sp. nov. These species are obligate pollinators of Phyllanthaceae plants. Photographs of adults and illustrations of genital structures are provided.